2007
DOI: 10.1021/ja0738125
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Preparation and Photophysical Characterization of Dimaleimide Dansyl Fluorogens:  Elucidation of the Maleimide Fluorescence Quenching Mechanism

Abstract: Dimaleimide fluorogens are being developed for application to fluorescent protein labeling. In this method, fluorophores bearing two maleimide quenching groups do not fluoresce until both maleimide groups have undergone thiol addition reactions with the Cys residues of the target protein sequence [J. Am. Chem. Soc. 2005, 127, 559-566]. In this work, a new convergent synthetic route was developed that would allow any fluorophore to be attached via a linker to a dimaleimide moiety in a modular fashion. Series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(129 citation statements)
references
References 38 publications
(45 reference statements)
7
121
0
1
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15] N-(1-Pyrenyl)maleimide is popularly used as a biological probe for fluorescent protein labeling, as well as the other maleimide derivatives functionalized with a variety of fluorophores. [16][17][18][19][20] Recently, alkynylpyrenes have been developed as improved pyrene-based biomolecular probes with high fluorescence quantum yields and reduced quenching of the fluorescence. [21][22][23] Recently, it was reported that the alternating copolymerization of N-alkylmaleimides (RMI) with isobutene (IB) produced high-molecular-weight copolymers [poly(RMIalt-IB)s] with excellent thermal stabilities, as well as excellent mechanical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] N-(1-Pyrenyl)maleimide is popularly used as a biological probe for fluorescent protein labeling, as well as the other maleimide derivatives functionalized with a variety of fluorophores. [16][17][18][19][20] Recently, alkynylpyrenes have been developed as improved pyrene-based biomolecular probes with high fluorescence quantum yields and reduced quenching of the fluorescence. [21][22][23] Recently, it was reported that the alternating copolymerization of N-alkylmaleimides (RMI) with isobutene (IB) produced high-molecular-weight copolymers [poly(RMIalt-IB)s] with excellent thermal stabilities, as well as excellent mechanical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, electron transfer dynamics from the dansyl to operator DNA has been studied. In principle, dansyl can also act as an electron donor or hole acceptor, retrieving the native state of guanine from its radical cation as the oxidation potential of N-ethyl dansylamide (0.94 V), a derivative of dansyl, is lower than the oxidation potential of guanine (58). The electron transfer dynamics of dansyl in the protein upon complexation with O R 1 and O R 2 DNA is evident from the faster fluorescence transients depicted in Figure 20 …”
Section: Differential Electron Transfer Dynamics In Specific Protein-mentioning
confidence: 99%
“…The reason for this is that the interaction with the analyte changes the redox potential of the quencher so that the photoinduced electron transfer is no longer possible and the fluorescence is restored. The two most prominent ways of annihilating a photoinduced electron transfer quenching system are either a chemical reaction (e.g., a Michael Type addition of a thiol on a maleimide analogue) [36][37][38] or the chelation of a cation (H + , Na + , K + , Ca 2+ , Zn 2+ , Cd 2+ , Hg 2+ , etc.). [5][6][7] Since these fluorescence activations are not photoinduced, we will not discuss them further.…”
Section: Photoinduced Electron Transfermentioning
confidence: 99%